2024
DOI: 10.1021/acsanm.4c00143
|View full text |Cite
|
Sign up to set email alerts
|

Bifunctional Calixarene-Decorated BODIPY-based Nanoporous Organic Polymers for the Efficient Photodegradation of Aqueous Organic Pollutants

Xin Wang,
Wuzi Zhao,
Shiyuan Zhou
et al.

Abstract: The increasingly severe wastewater pollution from an industry that contains organic dyes and phenols urges the development of sustainable removal technology. This work reports a bifunctional nanoporous organic polymer-based photocatalyst CABP by integrating a boron-dipyrromethene (BODIPY) chain polymer and a calixarene monomer into a polymer network. The CABP photocatalyst exhibits higher photodegradation competency toward bisphenol A and methylene blue (MB) than the linear polymer FBP. Noteworthily, good recy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 47 publications
(59 reference statements)
0
3
0
Order By: Relevance
“…These observations indicated that the post-modification of calixarene moieties not only endowed LBFD-2 with improved hydrophilicity and excellent swelling ability but also amplified its inherent photoelectrical properties. Compared to our previous work, a photocatalyst named CABP with two charge transfer channels, 19 LBFD-2 exhibited enhanced photocurrent and smaller radius of electrochemical impedance (Fig. S9, ESI†) owing to three charge transfer channels, highlighting that increased channels are beneficial for the separation and transport of carriers.…”
mentioning
confidence: 53%
See 2 more Smart Citations
“…These observations indicated that the post-modification of calixarene moieties not only endowed LBFD-2 with improved hydrophilicity and excellent swelling ability but also amplified its inherent photoelectrical properties. Compared to our previous work, a photocatalyst named CABP with two charge transfer channels, 19 LBFD-2 exhibited enhanced photocurrent and smaller radius of electrochemical impedance (Fig. S9, ESI†) owing to three charge transfer channels, highlighting that increased channels are beneficial for the separation and transport of carriers.…”
mentioning
confidence: 53%
“…The H 2 O 2 production rate of LBFD-2 was calculated to be 2.14 mmol g −1 h −1 in air and in the absence of any sacrificial agents, demonstrating its excellent H 2 O 2 generation ability, which primarily served as the source of ˙OH for efficient photodegradation. Compared to our previous work, 19 the photocatalytic H 2 O 2 production of LBFD-2 and subsequent photodegradation efficiency towards MB were both improved likely due to a more suitable pore size and better photoelectrochemical performance by multiple charge transfer channels (Fig. S19, ESI†).…”
mentioning
confidence: 57%
See 1 more Smart Citation